Ultrathin Broadband Metasurface Superabsorbers from a van der Waals Semimetal. Issue 4 (11th December 2022) - Alfieri, Adam D.; Motala, Michael J.; Snure, Michael; Lynch, Jason; Kumar, Pawan; Zhang, Huiqin; Post, Susanna; Bowen, Timothy; Muratore, Christopher; Robinson, Joshua A.; Hendrickson, Joshua R.; Glavin, Nicholas R.; et al.
Abstract: Metamaterials and metasurfaces operating in the visible and near‐infrared (NIR) offer a promising route towards next‐generation photodetectors and devices for solar energy harvesting. While numerous metamaterials and metasurfaces using metals and semiconductors have been demonstrated, semimetals‐based metasurfaces in the vis‐NIR range are notably missing. This work experimentally demonstrates a broadband metasurface superabsorber based on large area, semimetallic, van der Waals platinum diselenide (PtSe2 ) thin films in agreement with electromagnetic simulations. The results show that PtSe2 is an ultrathin and scalable semimetal that concurrently possesses high index and high extinction across the vis‐NIR range. Consequently, the thin‐film PtSe2 on a reflector separated by a dielectric spacer can absorb >85% for the unpatterned case and ≈97% for the optimized 2D metasurface in the 400–900 nm range making it one of the strongest and thinnest broadband perfect absorbers to date. The results present a scalable approach to photodetection and solar energy harvesting, demonstrating the practical utility of high index, high extinction semimetals for nanoscale optics. Abstract : This work demonstrates near‐unity average absorption over the visible to near infrared range by patterning sub‐20 nm thick, semimetallic platinum diselenide (PtSe2 ) films into arrays of nanoscale resonators. The large area PtSe2 films with extraordinary optical properties are grown and characterized. It is then demonstrated how combining dielectric and plasmonic resonances in a lossy material enables broadband absorption.